2022
DOI: 10.1177/1934578x221086988
|View full text |Cite|
|
Sign up to set email alerts
|

Antiviral Potential of Indian Medicinal Plants Against Influenza and SARS-CoV: A Systematic Review

Abstract: The COVID-19 pandemic has posed a significant threat to human health due to the lack of drugs that can potentially act against SARS-CoV -2. Also, even after the emergency approval of WHO, the vaccines’ efficacy is still a question, and people are getting reinfections. Previous studies have demonstrated the efficacy of traditional medicinal plants against influenza and SARS coronavirus. The present article aims to review potential phytochemicals from Indian medicinal plants that may be used against SARS-CoV-2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…65,66 In addition, many studies have investigated whether traditional medicinal plant extracts exhibit anti-SARS-CoV-2 activity. [67][68][69][70] Our experiments investigated the effects of CYP and monomer drugs on the proliferation ability of A549 cells at different times and found that longer treatment times and higher drug concentrations have a positive effect on the inhibition of A549 cell proliferation. With experimental durations of 24 h and 48 h, the IC50 values of CYP in A549 cells were 21.06 mg/mL and 12.73 mg/mL, respectively.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…65,66 In addition, many studies have investigated whether traditional medicinal plant extracts exhibit anti-SARS-CoV-2 activity. [67][68][69][70] Our experiments investigated the effects of CYP and monomer drugs on the proliferation ability of A549 cells at different times and found that longer treatment times and higher drug concentrations have a positive effect on the inhibition of A549 cell proliferation. With experimental durations of 24 h and 48 h, the IC50 values of CYP in A549 cells were 21.06 mg/mL and 12.73 mg/mL, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…65,66 In addition, many studies have investigated whether traditional medicinal plant extracts exhibit anti-SARS-CoV-2 activity. 67-70…”
Section: Discussionmentioning
confidence: 99%
“…As the disease progresses, cancer cells have the potential to infiltrate nearby tissues and lymph nodes and, in more advanced stages, disseminate through the bloodstream to distant organs, such as the lungs, liver, bones and brain, posing considerable challenges to effective treatment and prognosis [ 3 ]. The diagnosis of breast cancer involves a multifaceted approach, encompassing various methods [ 4 , 5 , 6 , 7 , 8 ]. Mammography, which utilises X-rays, is a pivotal screening tool for detecting lumps and abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…However, the side effects still need to be assessed for accurate interpretation [13][14][15][16][17][18]. During this study, we identified the compound name (2R,3R)- [19][20][21][22][23][24]. Further, the study was extended to the molecular dynamics simulation for 100ns and examined various outputs.…”
Section: Introductionmentioning
confidence: 99%